Evaluation of adipokines, oxidative stress, and inflammatory markers in gout patients - Fatma Ozer,; Fatih Baygutalp,; Muhammet Celik,; Nurcan Kılıc Baygutalp, (Archives of Rheumatology, 2025)
Objectives: This study aims to investigate the role of adipokines, oxidative stress, and inflammatory markers in the pathogenesis of gout. Patients and methods: Between September 2021 and December 2022, a total of 88 volunteers including 44 patients (37 males, 7 females; mean age: 56.5±11.6 years; range, 30 to 77 years) with gout disease and 44 age- and sex-matched healthy controls (37 males, 7 females; mean age: 54.3±12.1 years; range, 30 to 78 years) were retrospectively analyzed. Serum interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α), irisin, resistin, total oxidant status (TOS), and total antioxidant status (TAS) levels were analyzed. Results: The mean serum irisin levels were significantly higher in patients with gout than in the healthy controls (405.6±97.3 and 316.0±80.8 pg/mL, respectively). The mean IL-10 levels were significantly lower in patients with gout than in healthy controls (90.8±71.9 and 172.7±128.6 pg/mL, respectively). There was no statistically significant difference in the serum resistin, TNF-α, TOS, or TAS levels between the groups (p>0.05). Conclusion: Our study results show that serum irisin and IL-10 seem to be candidate biomarkers of diagnosis of gout.